2020
DOI: 10.1038/s41598-020-70918-x
|View full text |Cite
|
Sign up to set email alerts
|

Pentadecafluorooctanoic-acid-free polytetrafluoroethylene and mechanism of PFOA formation by γ-irradiation

Abstract: Low-molecular-weight (M w) polytetrafluoroethylene (PTFE) micropowder is added to wax for use in automotive equipment and printing machines and is produced by radiation-initiated degradation under atmospheric conditions. However, pentadecafluorooctanoic acid (PFOA) is produced as a by-product in concentrations greater than 25 ppb, which is problematic because PFOA does not degrade in the environment. Herein, we clarify the PFOA-formation mechanism and develop a manufacturing process for a novel low-M w PTFE mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…The observed spectra showed asymmetric signals, and they were assigned as peroxide macroradicals. These are a superposition of major asymmetric signals assigned from the middle-chain type peroxide macroradical and minor symmetric signals from the end-chain type peroxide macroradical, as already reported 16 – 18 . It was noticed that the signal intensity was more intense when the irradiation temperature was higher.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…The observed spectra showed asymmetric signals, and they were assigned as peroxide macroradicals. These are a superposition of major asymmetric signals assigned from the middle-chain type peroxide macroradical and minor symmetric signals from the end-chain type peroxide macroradical, as already reported 16 – 18 . It was noticed that the signal intensity was more intense when the irradiation temperature was higher.…”
Section: Resultssupporting
confidence: 73%
“…It was reported previously that the radical decay of PTFE accelerated with heat treatment 17 , 18 , the thermal stability of the fluoroalkyl and chain-end radicals are different, and the chain-end radicals were decayed faster 18 . It is suggested that the difference in the spectral shape in Fig.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations